Environmental modeling for sustainable regional development : system approaches and advanced methods - Ole, Vladimir (Information Science Reference, 2015)
This book presents methods and case studies for researchers and policy makers searching for alternative solutions for problems in regional sustainable development, taking into account socio-economic and environmental dimensions in a system integrated approach"--Provided by publisher.